2013
DOI: 10.1007/s00011-013-0667-3
|View full text |Cite
|
Sign up to set email alerts
|

OxLDL-induced IL-1beta secretion promoting foam cells formation was mainly via CD36 mediated ROS production leading to NLRP3 inflammasome activation

Abstract: These findings suggest that oxLDL-induced NLRP3 inflammasome activation mainly depends on CD36 involved in the progression of atherosclerosis by promoting oxLDL-mediated inflammation and foam cell formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(135 citation statements)
references
References 37 publications
12
115
1
7
Order By: Relevance
“…In the setting of ACS, it is possible that cholesterol crystals, present in atherosclerotic plaques and exposed after plaque rupture, induce inflammasome activation (5). However other factors such as the complement system (in particular C5a), TNFα (23), reactive oxygen species (24), and positive feedback from IL-1 or the inflammasome complex itself, which is released after cell apoptosis (25), may also contribute to inflammasome "priming". Indeed, the intense inflammatory milieu present in vulnerable atherosclerotic plaque might prime the inflammasome by several mechanisms, sustaining the inflammatory process.…”
Section: Increased Production Of Inflammasome-related Cytokines From mentioning
confidence: 99%
“…In the setting of ACS, it is possible that cholesterol crystals, present in atherosclerotic plaques and exposed after plaque rupture, induce inflammasome activation (5). However other factors such as the complement system (in particular C5a), TNFα (23), reactive oxygen species (24), and positive feedback from IL-1 or the inflammasome complex itself, which is released after cell apoptosis (25), may also contribute to inflammasome "priming". Indeed, the intense inflammatory milieu present in vulnerable atherosclerotic plaque might prime the inflammasome by several mechanisms, sustaining the inflammatory process.…”
Section: Increased Production Of Inflammasome-related Cytokines From mentioning
confidence: 99%
“…6) (120,136). Furthermore, oxLDL is involved in foam cell formation (103,116). One major source for ROS that is responsible for subendothelial oxidation processes is the NADPH oxidase complex of leukocytes, which converts O 2 into O 2 -.…”
Section: Protein Oxidation In Other Age-related Diseasesmentioning
confidence: 99%
“…* P < 0.05, *** P < 0.001 versus control; @@ P < 0.01, @@@ P < 0.001 low Ox-LDL versus high Ox-LDL; pro-IL-1 ␤ and mature IL-1 ␤ protein expression were signifi cantly attenuated by free radical scavenger NAC and NADPH oxidase INH DPI, it is quite possible that ROS play a role in IL-1 ␤ processing. Earlier studies have also shown that free radicals mediated caspase-1 activation and IL-1 ␤ production in THP1 monocytes and macrophages after Ox-LDL stimulation ( 7,46 ).…”
Section: Discussionmentioning
confidence: 92%
“…For studying the effect of Ox-LDL on cell lines expressing higher amounts of CD36, we used PMA-differentiated THP1 cells, which express high amounts of this receptor ( 46 ) and were also used in studies such as ( 7 ). Gene silencing with TLR2-, TLR4-, TLR6-, or CD36-specifi c siRNA in THP1 monocytes and macrophages signifi cantly attenuated Ox-LDL-induced PKC ␦ and IRAK1 activation and IL-1 ␤ production, suggesting that TLR2, TLR4, TLR6, and CD36 can mediate Ox-LDL-induced effects seen in the present study.…”
Section: Discussionmentioning
confidence: 99%